The Israeli Supreme Court and the Human Rights Revolution courts as agenda setters - Meydani, Assaf (Cambridge University Press, 2011)
"This book explains the reciprocal relations between the Supreme Court and the Israeli political system. It is based on a unique approach that contends that the non-governability of the political system and an alternative political culture are two key formal and informal variables affecting the behavior of several political players within the Israeli arena. The analysis illustrates the usefulness of such a model for analyzing long-term socio-political processes and explaining the actions of the players. Until this model changes significantly, the decisions of the High Court of Justice express the values of the state and enable Israel to remain a nation that upholds human rights. The court's decisions determine the normative educational direction and reflect Israel's democratic character with regard to the values of human rights"--Provided by publisher.